Cascading Globalization and Local Response: Indian Fishers' Response to Export Market Liberalization. (September 2015) - Axelrod, Mark; Roth, Brian; Kramer, Daniel Boyd; Salim, Shyam S.; Novak, Julia M.; Sathianandan, T. V.; Kuriakose, Somy
Scholars have long debated whether trade liberalization has positive or negative effects on resource use and ecosystems. This study examines the conditions under which resource use increases or decreases in response to reduced trade barriers, specifically after the 2008 World Trade Organization decision that led the United States to reduce anti-dumping duties on Indian shrimp. At the district level in South India, fishing fleet expansion was correlated with access to global market information via mobile phones. Model simulations indicate that increased mobile phone saturation could expand fishing effort sufficiently to deplete multiple marine species groups, while other species benefit from the loss of predators. However, scenario analysis suggests that regulatory interventions could mitigate these ecosystem pressures while still permitting fishers to benefit from increased access to global market information.